2019
DOI: 10.1002/lt.25405
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Split‐Liver Transplantation in a Nascent Framework of Deceased Donation

Abstract: Split-liver transplantation (SLT) is a valuable option for optimizing the use of good-quality deceased donor grafts. It is not routinely reported outside the West because of limited deceased donor numbers, technical and organizational constraints, lack of experience, and a predominant living donor liver transplantation (LDLT) practice. At our center, 20% of the liver transplantations (LTs) are from deceased donors. We report our experience of SLT and compare outcomes with pediatric and adult LDLT recipients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
(15 reference statements)
2
20
0
Order By: Relevance
“…Of note, we could not achieve sufficient graft survival in pediatric DDLT or split LT in comparison to LDLT in the present study. We need to learn from experienced countries regarding donor selection criteria, indications, procurement technique, preservation methods, and immunosuppression for pediatric DDLT and split LT. [27][28][29] The present study was associated with some limitations, including restrictions on information contained within the JLTS dataset, as well as the accuracy and consistency of that information. We did not have access to preoperative patient conditions, including the Pediatric End-Stage Liver Disease score, recipient or donor laboratory data, immunosuppression protocols, recipient or donor morbidity, surgical complications, and cause of death, growth, or quality of life (QOL) measures.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we could not achieve sufficient graft survival in pediatric DDLT or split LT in comparison to LDLT in the present study. We need to learn from experienced countries regarding donor selection criteria, indications, procurement technique, preservation methods, and immunosuppression for pediatric DDLT and split LT. [27][28][29] The present study was associated with some limitations, including restrictions on information contained within the JLTS dataset, as well as the accuracy and consistency of that information. We did not have access to preoperative patient conditions, including the Pediatric End-Stage Liver Disease score, recipient or donor laboratory data, immunosuppression protocols, recipient or donor morbidity, surgical complications, and cause of death, growth, or quality of life (QOL) measures.…”
Section: Discussionmentioning
confidence: 99%
“… 10 However, a meta‐analysis of adults revealed no differences, 11 and recent research suggested that adult recipient and allograft survival rates were similar, regardless of the allograft types used 12 . A prospective study in pediatric recipients exhibited no difference between SLT and LDLT groups 13 . As liver transplantation research in children is uncommon, and there is no standardized protocol, we herein retrospectively analyzed the impact of different allograft types on outcomes after PLT in patients with BA.…”
Section: Introductionmentioning
confidence: 93%
“…12 A prospective study in pediatric recipients exhibited no difference between SLT and LDLT groups. 13 As liver transplantation research in children is uncommon, and there is no standardized protocol, we herein retrospectively analyzed the impact of different allograft types on outcomes after PLT in patients with BA.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of scarcity of donor organs has led to optimization of the available grafts through various surgical techniques such as reduction of an adult donor graft in children, particularly through split liver grafts[ 79 ], auxiliary transplantation and the use of heterozygous donors.…”
Section: Surgical Considerationsmentioning
confidence: 99%